Simplified Summative Temporal Bone Dissection Scale Demonstrates Equivalence to Existing Measures. (January 2018) - Pisa, Justyn; Gousseau, Michael; Mowat, Stephanie; Westerberg, Brian; Unger, Bert; Hochman, Jordan B.
Introduction: Emphasis on patient safety has created the need for quality assessment of fundamental surgical skills. Existing temporal bone rating scales are laborious, subject to evaluator fatigue, and contain inconsistencies when conferring points. To address these deficiencies, a novel binary assessment tool was designed and validated against a well-established rating scale. Methods: Residents completed a mastoidectomy with posterior tympanotomy on identical 3D-printed temporal bone models. Four neurotologists evaluated each specimen using a validated scale (Welling) and a newly developed "CanadaWest" scale, with scoring repeated after a 4-week interval. Results: Nineteen participants were clustered into junior, intermediate, and senior cohorts. An ANOVA found significant differences between performance of the junior-intermediate and junior-senior cohorts for both Welling and CanadaWest scales ( P < .05). Neither scale found a significant difference between intermediate-senior resident performance ( P > .05). Cohen's kappa found strong intrarater reliability (0.711) with a high degree of interrater reliability of (0.858) for the CanadaWest scale, similar to scores on the Welling scale of (0.713) and (0.917), respectively. Conclusion: The CanadaWest scale was facile and delineated performance by experience level with strong intrarater reliability. Comparable to the validated Welling Scale, it distinguished junior from senior trainees but was challenged in differentiating intermediate and senior trainee performance.